Dual lidar wind measurements along an upstream horizontal line perpendicular to a suspension bridge. Issue 1 (November 2021) - Nafisifard, M; Jakobsen, J B; Cheynet, E; Snæbjörnsson, J T; Sjöholm, M; Mikkelsen, T
Abstract: Remote wind sensing can complement traditional anemometry at a bridge site and contribute to an improved wind-resistant design of long-span bridges. This study examines wind lidar measurement data recorded along a 168-meter-long horizontal line perpendicular to the main span of a suspension bridge in complex terrain. The velocity data records are obtained by a pair of continuous-wave Doppler lidars (short-range WindScanners) installed on the bridge deck. The measurement data are explored in terms of the mean wind speed and mean wind direction upstream of the bridge. The spectral characteristics of turbulence along the line are also investigated in relation to the increasing sampling volumes of a continuous-wave lidar system at increasing distances from the monitored area. Wind characteristics observed by the lidars are compared to those derived from sonic anemometer data recorded above the bridge deck at midspan. The results provide new insight into the wind flow characteristics in a fjord and demonstrate the potential of lidar measurements in charting the wind flow around a bridge. A slight monotonic increase of the wind speed, as well as a decrease in the yaw angle, is observed as the distance to the bridge reduces from 160 m to 20 m, while lower wind velocities are accompanied by a more stable wind direction. Within 15 m from the bridge deck, the adopted lidar setup gives unreliable information due to the large angle between the lidar beams.